Hereditarily Irreducible Mappings of Cartesian Product of Continua - Lončar, Ivan (Sarajevo Journal of Mathematics, 2024)
In Section 2 we shall prove that if Cartesian product $X× Y$ of nondegenerate continua admits a hereditarily irreducible mapping $f:X× Y→ Z,$ then w$(X× Y)$=w$(Z)$. The main section of the paper, Section 3, contains theorems concerning the Whitney maps on continua. In particular, it is proved that the product $Π \{X_{s}:s\in S\}$ of nondegenerate continua admits a Whitney map for $C(Π \{X_{s}:s\in S\})$ if and only if it is metrizable. 2000 Mathematics Subject Classification. Primary 54B20, 54F15